2022
DOI: 10.1007/s10508-022-02386-5
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Gender-Related Cognition, Gender Dysphoria, Autistic-Like Traits, and Mentalizing: Differences Between Autistic and Non-Autistic Cisgender and Transgender Adults

Abstract: Evidence indicates a link between autism spectrum disorder (ASD) and gender diversity, yet this intersection remains insufficiently understood. Here, we investigated whether (1) ASD affects gender-related cognition (i.e., mental processes of perceiving and interpreting one’s own gender self-concept), (2) autistic people have increased gender dysphoria and recall limited gender-typed behavior from childhood, and (3) transgender individuals have increased ASD-like traits and difficulties in mentalizing. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…We should note that the participant groups were the same as those reported in . 16 Yet, we did not report any findings related to alexithymia in the aforementioned paper. The School of Psychology Research Ethics Committee at the University of Kent has approved this study (ID: 201915670711375862).…”
Section: Participantsmentioning
confidence: 68%
See 2 more Smart Citations
“…We should note that the participant groups were the same as those reported in . 16 Yet, we did not report any findings related to alexithymia in the aforementioned paper. The School of Psychology Research Ethics Committee at the University of Kent has approved this study (ID: 201915670711375862).…”
Section: Participantsmentioning
confidence: 68%
“…15 Furthermore, research has shown an elevated number of autistic traits in non-autistic transgender and gender diverse people relative to non-autistic cisgender people. 16,17 There are also a number of transgender and gender diverse people who report clinical levels of autistic traits but do not meet the full diagnostic criteria for autism, forming a subclinical autistic group. 18,19 Lastly, research has found evidence of increased rates of transgender and gender diverse people in autistic samples, 20 and increased gender dysphoric feelings in cisgender autistic adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of this study is that autism diagnostic status was based on one self-reported question for autism rather than best evidence-based assessment practices which include the use of multi-informant and multi-method approaches. One recent study suggests that a diagnosis of autism spectrum disorder may be overestimated within GM populations when assessed for via self-report only (Kallitsounaki & Williams, 2022). At the same time, it is also possible that individuals who both self-identify as autistic and experience similar difficulties as autistic people with a formal diagnosis of autism may not have endorsed having an autism spectrum disorder due to challenges with receiving a formal diagnosis.…”
Section: Limitations/future Directionsmentioning
confidence: 99%
“…In addition, this study used only one question asking participants' gender identity, and items about biological sex were not considered, which means this study may have missed individuals identifying as transgender and/or individuals who were in the process of transitioning in our groupings. Recent studies have shown that adults who identify as transgender are more likely to report a mental health diagnosis and/or a diagnosis of autism comparative to their cisgender adult peers (Kallitsounaki & Williams, 2022;Warrier et al, 2020).…”
Section: Limitations/future Directionsmentioning
confidence: 99%